The Designing of a Learning Theory to Promote a Classroom Pedagogy for Moodle Self-Directed Learning - Yeyisani Evans Makhubele; Judah Paul Makonye (STKIP Singkawang, 2022)
The higher education institutions across the world have changed their teaching and learning methods due to the Covid19 pandemic. They are now using different learning management systems like Moodle. The implication of the sudden transition to online learning is that students now have to become more independent, and self-directed in their learning. The aim of this paper is therefore to develop a Moodle (Modular Object Oriented Dynamic Learning Environment) Self-Directed Learning Theory. It explores some of the learning aspects related to the development of students towards Moodle self-directed learning and proposes a framework of skills that lecturers and teachers can use as a guide to increasing student responsibility. This study is situated within the theory of Instrumental Genesis (IG). The researchers employed the design-based research method when developing this learning theory. The process of developing this learning framework involved a literature review of Moodle and self-directed learning theories. The study of the learning theories revealed various Moodle and self-directed perspectives which were used to develop this learning theory. The outcome of this study is a learning theory that will hopefully promote self-directed learning within the context of Moodle teaching and learning.